Successful Treatment of Multifocal Histiocytic Sarcoma Occurring after Renal Transplantation with Cladribine, High-Dose Cytarabine, G-CSF, and Mitoxantrone (CLAG-M) Followed by Allogeneic Hematopoietic Stem Cell Transplantation. (8th June 2015) - Tomlin, Julia; Orosco, Ryan K.; Boles, Sarah; Tipps, Ann; Wang, Huan-You; Husseman, Jacob; Wieduwilt, Matthew
Abstract : Histiocytic sarcoma (HS) is a rare, aggressive malignancy. Lesions previously called HS were typically non-Hodgkin lymphomas, not HS. As such, chemotherapy directed at lymphoid neoplasms was frequently successful, but it is unclear if these regimens are ideal for HS. We present a 33-year-old African gentleman who underwent sequential renal transplants for glomerulonephritis. He subsequently developed HS of the upper airway and multiple cutaneous sites. The patient received cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) followed by salvage ifosfamide, carboplatin, and etoposide (ICE) but had continuous progression of cutaneous involvement. Cladribine, high-dose cytarabine, G-CSF, and mitoxantrone (CLAG-M) yielded a partial response with near resolution of disease. Ultimately, the patient achieved a complete remission after myeloablative allogeneic hematopoietic stem cell transplant. HS occurring after solid organ transplant raises the possibility of HS as a potential posttransplant malignancy. The use of CLAG-M has not been reported in HS. In this case, histiocyte-directed chemotherapy with CLAG-M was superior to lymphoma-directed regimens.